PSVII-4 Flavoured drinking water improves performance of post-weaned piglets. (8th October 2021) - Luna, Fabrina S; Silva, Bruno Alexander N; Moraes, Elenice A; Carvalho, Debora Cristine O; Jacob, David V; Eskinazi, Simon; Domingos, Rodrigo L; Carvalho, Illa Carla S; Cardoso, Hysla M; Cardoso, Larissa A; Rebordoes, Flavio Igor G; Gonçalves, Mateus F
Abstract: Water is an absolute requirement in the daily needs of the pig. It has been suggested that after weaning, pigs may not consume enough water which impacts in their hydration. It is commonly known that providing water to piglets encourages higher feed intake and improves nutrient absorption, with a positive impact on weight gain and on post-weaning feed intake adaptation, decreasing problems caused by the transition phase from the farrowing unit to the nursery. The objective of this study was to evaluate the effect of the addition of a flavor to the drinking water of piglets on their voluntary water intake and performance in the first week after weaning. Sixty (30 males and 30 females) commercial piglets were used, in a randomized block design, with 10 repetitions per treatment (with or without addition of 100g/ 1000 L of water of Power sweet ® ; Adisseo) and each repetition with 3 animals. The piglets were weighed at weaning and d 8 post weaning. Parameters evaluated were the initial and final weight; daily weight gain; average daily and total feed intake; total daily and average consumption per animal of water and correlation between feed and water consumption. The means of the variables were submitted to the Pdiff option of the SAS using the Tukey test for contrasts (P < 0.05). The addition of a flavor in the drinking water increased daily weight gain in 6.7% (P = 0.041), average daily feed consumption in 2.98% (P = 0.0014), total feed consumption in 2.96% (P = 0.0014) and increased the final weight by 1.25% (P = 0.0411) when compared the control. Feed and water intake had a positive correlation in both treatments. The addition of flavor to the drinking water increases feed and water intake, improving the piglet performance in the first week after weaning.